THE POWER OF SOUND: UNDERSTANDING ONOMATOPOEIC WORDS (Ta'limning zamonaviy transformatsiyasi, 2024)
Abstract: Onomatopoeic words are linguistic expressions that imitate the natural sounds associated with the objects or actions they represent. This article delves into the nature of onomatopoeic words, their role in various languages, and their importance in enhancing communication. Examples from everyday life, literature, and popular culture illustrate how these words capture the essence of sound and evoke vivid imagery. The article also explores the scientific and psychological aspects of onomatopoeia, shedding light on why humans use these words to make language more dynamic and relatable.